Pembentukan Karakter Religius Siswa Melalui Kegiatan Dewan Jama'ah Mushola (DJM) Di SMK PGRI 2 Kota Kediri - Sulistiyorini, Defi; Nurfalah, Yasin (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2019)
This study aims to determine the formation of the religious character of students through the activities of the Jamaah Mushola Council (DJM) at SMK PGRI 2 Kota Kediri. This study departs from three questions,